Climate Change Adaptation, Risk Management and Sustainable Practices in the Himalaya - Sharma, Sanjeev; Kuniyal, Jagdish Chandra; Chand, Pritam; Singh, Pardeep (Cham : Springer International Publishing : Imprint: Springer, 2023)
This volume analyzes ecological and socio-economic risks due to climate change in the Himalayan mountain ecosystems, communities, and proposes adaptation strategies and sustainability practices. In order to better understand the potential actions required to improve natural resource conservation and the development of mountain people's livelihoods. The authors discuss the current status of local knowledge system on various environmental aspects of conservation and sustainable use of mountain resources in the Himalaya. The book addresses the institutional capacities, gaps, and priority areas of capacity building to strengthen policies and governance in regard to climate change, landuse management, biodiversity conservation, and sustainable management in the Himalayan region. The aim of this book is to enhance coordination building among policymakers, planners, mountain communities to foster collaboration between different stakeholders by understanding local perceptions of climate change as well as variability issues, and establishing adaptation strategies to cope with these impacts. The chapters incorporate theoretical and applied aspects, and may serve as baseline information for the sustainability of mountain ecosystems through the contribution of multidisciplinary and interdisciplinary expertise from the Himalayan region. The book will be useful for students, teachers, and researchers working in different areas pertaining to mountain ecosystems, as well as policymakers and planners working on issues related to the sustainability of the mountain ecosystem.
1-Introduction: Climate Change, adaptation and risk management for the mountain sustainability -- 2-Dynamics of demographic, socio-cultural, economic and ecological aspects -- 3-Indigenous knowledge system and traditional sustainable management practices in the Himalayan region -- 4-Anthropogenic intervention, globalized economic development impacts and trans border political issues in the Himalaya -- 5-Urbanization, migration and assessment of the carrying capacity of Himalayan mountain ecosystem -- 6-Environmental degradation and ecological instability: Issues, challenges and way forwarded in the Himalaya -- 7-Climate change, natural hazards and dynamics of landscape changes -- 8-Socio-economic, livelihood and ecological transformation in the Himalayan region -- 9-Human-animal conflicts and wildlife management in the Himalaya -- 10-Climate Change in glacial, periglacial and paraglacial regions of the Himalaya -- 11-Climate induced and geophysical disasters, and risk reduction management in mountains regions -- 12-Available field-based, geophysical and geospatial tools and techniques, their applied practice, strengths, and limitations to study Mountain environment -- 13-Millennium to centennial to contemporary period climate trends and associated climatic variability over the mountain areas of Himalaya -- 14-Regional variation of climatic changes and associated environmental modifications -- 15-Mountain policy, law, governance and role of Institutional and organization for sustaining Himalayan mountain ecosystem -- 16-Interface of technology-science-policy-society and environmental sustainability in the Himalaya -- 17-Integrated ecological restoration, upstream-downstream integration and sustainable development in the Himalaya -- 18-Integrated planning for mountain sustainability and sustainable development: new challenges, innovative approaches and way forward -- 19-Climate change coping strategies and climate smart communities adaptation in the Mountain ecosystem -- 20-Environmental Governance for Environmental Sustainability of Mountainous regions.
Keywords: Climatology; Environmental management; Sustainability; Economic policy; Social policy; Climate Sciences; Environmental Management; Sustainability; Socio-Economic Policy